(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article considers the factors of humanization of the living environment as one of the main principles of the sustainable development strategy of Odesa. Improving the urban structure in order to achieve physical, psychological and spiritual comfort of a person in an artificial environment demonstrates a human-centered approach to finding an integrated, comprehensive (economic, social, energy, economic, transport, etc.) model of a city with a high level of environmental quality. The analysis is focused on studying the current state of Odesa and finding solutions to overcome the antagonism and confrontation between the existing conditions and the universal human needs of its residents. It has been determined that humanization is based on taking into account the biological, physiological, spiritual, aesthetic, psychological and socio-cultural aspects of human needs; it is based on social, environmental, ergonomic, functional, aesthetic, constructive, technological, economic requirements for improving the living environment and provides conditions for the formation of an environmentally, psychologically and aesthetically comfortable environment by urban planning means. The results obtained will contribute to the development of a program for the further development of residential areas of Odesa, their reconstruction and transformation into a comfortable, dignified and humane environment of the 21st century that best meets the level of human needs.